Gerakan World Cleanup Day sebagai Wujud Kepedulian terhadap Lingkungan Hidup - Khumairatun Nisa, Nadia; Hertanto, Hertanto; Budiono, Pitojo; Makhya, Syarief; Rosalia, Feni (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
World Cleanup Day is an environment-based social movement that aims to free the earth from waste and ultimately become a movement for mitigation and adaptation to climate change. Waste is the main problem in Bandar Lampung City due to the dominance of human activities. The purpose of this study is to see the World Cleanup Day movement as a form of concern for the environment in Bandar Lampung City. This study uses the library research method with documentation data collection techniques and data analysis using content analysis. The results of the study show that the World Cleanup Day movement views nature as a home so that all its resources are needed by humans more than they know. The waste problem is the result of uncontrolled human activities, so the best collective action is needed to fix it. The values of this movement are Cooperation, Positivity, Leadership, Technology, and Fun. This movement is present as an act of triggering positive mindset changes and actions to increase public awareness of the waste problem in Bandar Lampung City. The World Cleanup Day movement collaborates with the government, volunteers (community), and other communities. So far the implementation of the movement has been running optimally.